Species cohesion of an extremophyte (Carex angustisquama, Cyperaceae) in solfatara fields maintained under interspecific natural hybridization. (9th June 2021) - Nagasawa, Koki; Setoguchi, Hiroaki; Maki, Masayuki; Sawa, Kazuhiro; Horie, Kenji; Sakaguchi, Shota
Abstract: Background and Aims: Hybridization is the main driver of plant diversification, and gene flow via hybridization has multifaceted effects on plant evolution. Carex angustisquama is an extremophyte that grows on soils heavily acidified by volcanism. Despite its habitat distinct from that of other species, this species is known to form interspecific hybrids, implying interspecific gene flow. It is crucial to verify the extent and direction of interspecific gene flow between C. angustisquama and closely related species to understand the evolutionary process of an extremophyte in solfatara fields. Methods: In this study, expressed sequence tag–simple sequence repeat markers were utilized to infer the extent and direction of interspecific gene flow between C. angustisquama and closely related species. Key Results: Bayesian clustering and simulation analyses revealed that all individuals of the three hybrid species were classified into the first hybrid generation or first backcross to C. angustisquama ; therefore, current interspecific gene flow is limited. Moreover, in the Bayesian inference of historical gene flow based on multispecies samples, the model that assumed no interspecific gene flow was the most strongly supported across all species pairs, including phylogenetically close but ecologically distinctive species pairs. Conclusions: Our results revealed that interspecific gene flow between C. angustisquama and its related species has been limited both currently and historically. Moreover, our results of Bayesian inference of historical gene flow indicated that extrinsic, rather than intrinsic, factors probably act as isolating barriers between Carex species, with hybrid breakdown via microhabitat segregation being the probable potential barrier. Overall, our findings provide insights into the evolutionary process of an extremophyte in solfatara fields and offer an important example of the mechanisms of diversification of the speciose genus Carex .